Complete mitochondrial genome analysis of Lingula anatina from Korea (Brachiopoda, Lingulida, Lingulidae) - Mustafa Zafer Karagozlu; Seong-Geun Kim; Do Dhin Thinh; Chang-Bae Kim (Mitochondrial DNA. Part B. Resources, 2017)
In this study, complete mitochondrial genome of the Lingula anatina (Lamark, 1801) from Korea has been sequenced and analysed, and compared with previous complete mitochondrial genome record from Japan. The mitogenome is 25,790 bp and composed of 13 protein-coding genes, two ribosomal RNA and 34 tRNA. In comparison with previous record, there are dramatically changes in structure between two records. Additionally, phylogenetic tree of L. anatina in Brachiopoda reconstructed due to 12 protein-coding genes of mitochondrial genome. The results showed that the Korean L. anatina positioned in Brachiopoda and the closest species is the L. anatina from the Japan. This study provides the second complete mitochondrial genome for the species.